2010
DOI: 10.1083/jcb.200910142
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of the Dam1 and Ndc80 kinetochore complexes enhances microtubule coupling and is regulated by aurora B

Abstract: The Dam1 complex, regulated by aurora B phosphorylation, confers a more stable microtubule association for the Ndc80 complex at kinetochores (see also related paper by Lampert et al. in this issue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
302
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(318 citation statements)
references
References 45 publications
15
302
1
Order By: Relevance
“…Previous work found that addition of the 10-member outer kinetochore Dam1 complex increased the residence time of Ndc80c 2.6-fold, to 6.4 ± 0.2 s (Fig. 3 A and B) (24). Surprisingly, we found that MIND also dramatically affected the microtubule binding of Ndc80c because the residence time of MIND-GFP/ Ndc80c complexes was 10.4 ± 0.6 s, fourfold longer than that of Ndc80c-GFP (Fig.…”
Section: Mind Activates Microtubule Binding By Ndc80c Via a Mechanismcontrasting
confidence: 40%
“…Previous work found that addition of the 10-member outer kinetochore Dam1 complex increased the residence time of Ndc80c 2.6-fold, to 6.4 ± 0.2 s (Fig. 3 A and B) (24). Surprisingly, we found that MIND also dramatically affected the microtubule binding of Ndc80c because the residence time of MIND-GFP/ Ndc80c complexes was 10.4 ± 0.6 s, fourfold longer than that of Ndc80c-GFP (Fig.…”
Section: Mind Activates Microtubule Binding By Ndc80c Via a Mechanismcontrasting
confidence: 40%
“…Although Dam1 and Ndc80 do not interact in solution, Dam1 enhances the binding of Ndc80 to MTs and imparts to it the ability to track with depolymerizing MT ends (26)(27)(28). Interestingly, Ndc80-coated beads supplemented with soluble Dam1 can withstand, on average, only a 4.4-pN load, with the largest measured force of 9 pN (26).…”
Section: Discussionmentioning
confidence: 99%
“…The Dam1 complex binds MTs in vivo and in vitro and localizes to the KT in a MT-dependent fashion (Li et al 2002). The Dam1 complex, at high concentrations in vitro, oligomerizes into a closed-ring structure that encircles MTs (Miranda et al 2005;Lampert et al 2010;Tien et al 2010). There is an interaction between Dam1 and Ndc80 complexes on MTs in vitro that enhances the ability of Ndc80 to maintain MT attachments (Lampert et al 2010;Tien et al 2010).…”
mentioning
confidence: 99%
“…Recombinant Ndc80 complex binds MTs in vitro, and the activity is restricted to the head domains of Nuf2 and Ndc80 (Wei et al 2005;Ciferri et al 2008). Yeast has an additional protein complex, Dam1, composed of 10 proteins, that is also required for KT-MT attachment (Westermann et al 2006;Lampert et al 2010;Tien et al 2010). The Dam1 complex binds MTs in vivo and in vitro and localizes to the KT in a MT-dependent fashion (Li et al 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation